The Influence of Financial Literacy, Credit Requirements, and Financial Report Quality on Access to Financing for Micro, Small and Medium Enterprises - Resti Gustika; Rinofah, Risal; Maulida, Alfiatul (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study examines the influence of financial literacy, credit requirements, and the quality of financial reports on access to financing for MSMEs in the micro-trade sector in Yogyakarta City. Using a quantitative approach, data were collected from 80 MSME respondents selected through purposive sampling. Data were gathered via questionnaires with a Likert scale and analyzed using Partial Least Square (PLS) version 4.0 to evaluate the measurement and structural models. The findings reveal that financial literacy significantly influences access to financing, indicated by a T-statistic of 2.234 and a P-value of 0.026. This suggests that higher financial literacy among MSME owners facilitates easier access to financing. Credit requirements also significantly affect access, with a T-statistic of 3.259 and a P-value of 0.001, highlighting the impact of complex credit conditions on MSME financing accessibility. However, the quality of financial reports does not significantly affect access, as shown by a T-statistic of 1.057 and a P-value of 0.290, implying that financial reports are not the primary factor in credit decisions for MSMEs. This study emphasizes the importance of improving financial literacy and addressing credit requirements to enhance financing access for MSMEs.